The Effectiveness of Content Mastery Services on Career Self-Understanding for High School Graduates Who Do Not Pursue Higher Education - Aziza, Riska; Syahputra, Irwan (Journal of Educational Sciences, 2025)
This study aims to measure the effectiveness of mastering content services about career self-understanding among high school graduates who do not continue to higher education. The main focus of the research is how these content services can help adolescents recognize their interests, abilities, work values, personality, and life roles as a basis for making appropriate career decisions. The method used is a quantitative approach with a pretest and post-test design on a sample of high school graduates who have participated in the career self-understanding content services. The results show a significant improvement in mastering the concept of career self-understanding after participating in the content services. These findings indicate that effectively designed content services can be a useful tool for adolescents who do not pursue higher education in planning and developing their careers independently. The practical implication of this study is the importance of providing structured career content services to support adolescents' transition to the workforce or other alternative pathways.